2010
DOI: 10.3390/cancers2020859
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in Stem, Cancer, and Cancer Stem Cells

Abstract: The term ‘‘oxidative stress” refers to a cell’s state characterized by excessive production of reactive oxygen species (ROS) and oxidative stress is one of the most important regulatory mechanisms for stem, cancer, and cancer stem cells. The concept of cancer stem cells arose from observations of similarities between the self-renewal mechanism of stem cells and that of cancer stem cells, but compared to normal stem cells, they are believed to have no control over the cell number. ROS have been implicated in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
0
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 148 publications
(176 reference statements)
2
142
0
21
Order By: Relevance
“…These adaption mechanisms are hypothesized to be responsible for radiation resistance in tumor therapy that targets cancer cells through induction of oxidative stress (Huang et al 2012). Even though the redox status of CSCs is largely unknown, it was shown that adult stem cells have a lower level of ROS than more mature cells, probably to maintain the stem cell character (Dayem et al 2010, Huang et al 2012. Therefore, it is assumed that CSCs have upregulated levels of antioxidant scavenger mechanisms that protect CSCs and contribute to radiation therapy resistance (Ogawa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These adaption mechanisms are hypothesized to be responsible for radiation resistance in tumor therapy that targets cancer cells through induction of oxidative stress (Huang et al 2012). Even though the redox status of CSCs is largely unknown, it was shown that adult stem cells have a lower level of ROS than more mature cells, probably to maintain the stem cell character (Dayem et al 2010, Huang et al 2012. Therefore, it is assumed that CSCs have upregulated levels of antioxidant scavenger mechanisms that protect CSCs and contribute to radiation therapy resistance (Ogawa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The melting points were determined on capillary tubes on a Büchi oil heated melting point apparatus (Essen, Germany) and uncorrected. 1 H NMR and 13 C NMR spectra were performed on Varian-Mercury 400 MHz spectrophotometer (Varian, Darmstadt, Germany) in DMSO-d 6 using TMS as internal. Splitting patterns were designated as follows: s: singlet; d: doublet; m: multiplet.…”
Section: Chemistrymentioning
confidence: 99%
“…Free radicals are mainly generated by metabolic processes in the human body, and some radicals have essential roles in normal cell processes such as neural signal transduction 1 . On the other hand, excessive free radical incursion, causing very important diseases, can damage all components of the cell including DNA, proteins, and lipids 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Products derived from this injury are used as biomarkers of oxidative stress in the assessment and diagnosis of all cancers. Especially breast cancer (Gonenc et al, 2005;Dayem et al, 2010;Sosa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%